Scoping review of grief studies in Indonesia - Christina Yeni Kustanti; Nurlia Ikaningtyas; Ninik Yunitri; Hidayat Arifin; Mei Rianita Elfrida Sinaga; Eka Kristina Asi; Nimsi Melati; Henny Dwi Susanti (JKP (Jurnal Keperawatan Padjajaran), 2023)
Background: One death can cause nine bereavements. Considering the impact of human loss, studies on grief are crucial for better bereavement care services.